Effect of acetylated distarch adipate on the physicochemical characteristics and structure of shrimp (Penaeus vannamei) myofibrillar protein. (30th March 2022) - Mi, Jie; Ni, Wei; Huang, Ping; Hong, Jingxia; Jia, Ru; Deng, Shanggui; Yu, Xunxin; Wei, Huamao; Yang, Wenge
Highlights: The addition of 1.0 % ADA enhanced gel strength of MPG significantly. Excessive additives made the structure of MP more fragile. ADA could reduce the relaxation time (T2 ) of MPG. Heating changed the secondary structure of MPG significantly. There is a positive correlation between gel strength and T2b . Abstract: To investigate the effect of acetylated distarch adipate (ADA) on the physicochemical properties and structure of shrimp myofibrillar protein (MP), the changes in chemical bonds, secondary structure and protein composition of shrimp MP and MP gel (MPG) were analyzed. Besides, the microstructure, water state, texture properties and water holding capacity (WHC) of MPG with different ADA additions were compared. The results showed that the shrimp MPG with 1% ADA addition had the highest breaking force and gel strength, WHC, and the densest three-dimensional network structure. The ADA had little significant effect on the secondary structure of MP and MPG. In addition, hydrogen and ionic bonds were the main chemical bonds of MP, while MPG is mainly dominated by hydrophobic and disulfide bonds. The correlation analysis of gel properties and water state of MPG showed that bound water and immobilized water had a positive effect on the gel strength.